Z-Guggulsterone Produces Antidepressant-Like Effects in Mice through Activation of the BDNF Signaling Pathway - Liu, Feng-Guo (Int J Neuropsychopharmacol, 2017)
BACKGROUND: Z-guggulsterone, an active compound extracted from the gum resin of the tree Commiphora mukul, has been shown to improve animal memory deficits via activating the brain-derived neurotrophic factor signaling pathway. Here, we investigated the antidepressant-like effect of Z-guggulsterone in a chronic unpredictable stress mouse model of depression. METHODS: The effects of Z-guggulsterone were assessed in mice with the tail suspension test and forced swimming test. Z-guggulsterone was also investigated in the chronic unpredictable stress model of depression with fluoxetine as the positive control. Changes in hippocampal neurogenesis as well as the brain-derived neurotrophic factor signaling pathway after chronic unpredictable stress/Z-guggulsterone treatment were investigated. The tryptophan hydroxylase inhibitor and the tyrosine kinase B inhibitor were also used to explore the antidepressant-like mechanisms of Z-guggulsterone. RESULTS: Z-guggulsterone (10, 30 mg/kg) administration protected the mice against the chronic unpredictable stress-induced increases in the immobile time in the tail suspension test and forced swimming test and also reversed the reduction in sucrose intake in sucrose preference experiment. Z-guggulsterone (10, 30 mg/kg) administration prevented the reductions in brain-derived neurotrophic factor protein expression levels as well as the phosphorylation levels of cAMP response element binding protein, extracellular signal-regulated kinase 1/2, and protein kinase B in the hippocampus and cortex induced by chronic unpredictable stress. Z-guggulsterone (10, 30 mg/kg) treatment also improved hippocampal neurogenesis in chronic unpredictable stress-treated mice. Blockade of the brain-derived neurotrophic factor signal, but not the monoaminergic system, attenuated the antidepressant-like effects of Z-guggulsterone. CONCLUSIONS: Z-guggulsterone exhibits antidepressant activity via activation of the brain-derived neurotrophic factor signaling pathway and upregulation of hippocampal neurogenesis.